The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1143/jjap.34.l1482
|View full text |Cite
|
Sign up to set email alerts
|

Surface Alteration of Amorphous Si3N4 Films by ArF Excimer Laser Irradiation

Abstract: We report on the electron spin resonance (ESR) study of the photo-oxidative stress-mediated protein conformation changes in the spin-labelled protein staphylococcal nuclease (SNase). The photo-oxidative stress was brought on by photosensitization of singlet oxygen ( 1 g ) in the presence of a novel photosensitizer, water-soluble fullerol C 60 (OH) 19 (ONa) 17 , and resulted in partial protein denaturation. This process was monitored via ESR measurements performed for a spin-labelled SNase Thr-62-Cys mutant, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…It is found that experimental data are very closely located on a single curve. When the NH3 surface reaction proceeds according to a first-order reaction including an initial small and very fast reaction, the N atom concentration is given by (Nsat -Njflexp(-k203t)} + 1V [6] where N4 is the N atom concentration in saturation, N1 is the N atom concentration at the initial nitridation within a minute of NH3 exposure, and k2 is the nitridation rate constant. The solid line in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is found that experimental data are very closely located on a single curve. When the NH3 surface reaction proceeds according to a first-order reaction including an initial small and very fast reaction, the N atom concentration is given by (Nsat -Njflexp(-k203t)} + 1V [6] where N4 is the N atom concentration in saturation, N1 is the N atom concentration at the initial nitridation within a minute of NH3 exposure, and k2 is the nitridation rate constant. The solid line in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that thermal nitridation of SiO, using NH3 proceeds via the replacement of oxygen by nitrogen atoms under the action of hydrogen.' When the NH3 surface reaction proceeds according to a first-order reaction including an initial small and very fast reaction, the N atom concentration is given by (Nsat -Njflexp(-k203t)} + 1V [6] where N4 is the N atom concentration in saturation, N1 is the N atom concentration at the initial nitridation within a minute of NH3 exposure, and k2 is the nitridation rate constant. Therefore, it is expected that oxygen did not play a significant role in the present experiments on the nitridation of Si.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For these reasons, formation of SiN at low temperature is strongly required. A lot of groups have proposed to form SiN at low temperatures by electron beam induced nitridation [6], excimer -laser enhanced nitridation [7,8] and plasma enhanced CVD [9,10]. However, these excitation methods may induce damage in the formed nitride film and/or surface of substrates.…”
Section: Introductionmentioning
confidence: 99%